2017
DOI: 10.1074/jbc.m117.799593
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase-type plasminogen activator (uPA) is critical for progression of tuberous sclerosis complex 2 (TSC2)-deficient tumors

Abstract: Lymphangioleiomyomatosis (LAM) is a fatal lung disease associated with germline or somatic inactivating mutations in tuberous sclerosis complex genes ( or ). LAM is characterized by neoplastic growth of smooth muscle-α-actin-positive cells that destroy lung parenchyma and by the formation of benign renal neoplasms called angiolipomas. The mammalian target of rapamycin complex 1 (mTORC1) inhibitor rapamycin slows progression of these diseases but is not curative and associated with notable toxicity at clinicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 119 publications
0
15
0
Order By: Relevance
“…4b, c). In the in vivo tumorigenicity assays, inhibitors were used to suppress the activities of AMPK and/or FOXO3 17 . Consistent with the in vitro findings, suppressing both AMPK and FOXO3 in SIRT1-overexpressing xenograft tumors substantially reversed the improved cisplatin sensitivity, as indicated by the tumor volumes and TUNEL staining ( Fig.…”
Section: Fig 3 Sirt1 Inhibits Csc Properties Of Gc Cells a Bmentioning
confidence: 99%
“…4b, c). In the in vivo tumorigenicity assays, inhibitors were used to suppress the activities of AMPK and/or FOXO3 17 . Consistent with the in vitro findings, suppressing both AMPK and FOXO3 in SIRT1-overexpressing xenograft tumors substantially reversed the improved cisplatin sensitivity, as indicated by the tumor volumes and TUNEL staining ( Fig.…”
Section: Fig 3 Sirt1 Inhibits Csc Properties Of Gc Cells a Bmentioning
confidence: 99%
“…The abnormal expression of the uPA system has been detected in breast cancer, prostate cancer, ovarian cancer, and lung cancer ( 84 ), and was recently reported in TSC-deficient tumors. The study found that overexpression of uPA was a direct consequence of TSC mutation in LAM cells and mTOR inhibitors even increased expression of uPA in cells with compromised TSC function ( 85 ). However, inhibition of uPA expression in TSC2-null tumor cells could not only reduce their invasive and mitogenic potentials but also increase their susceptibility to the pro-apoptotic agent simvastatin ( 85 ).…”
Section: Emt Process In Lam Metastasismentioning
confidence: 99%
“…The study found that overexpression of uPA was a direct consequence of TSC mutation in LAM cells and mTOR inhibitors even increased expression of uPA in cells with compromised TSC function ( 85 ). However, inhibition of uPA expression in TSC2-null tumor cells could not only reduce their invasive and mitogenic potentials but also increase their susceptibility to the pro-apoptotic agent simvastatin ( 85 ). Together, these studies indicate that uPA might serve as a potential target to prevent the dissemination of tumor cells and the progression of disease in LAM treatment.…”
Section: Emt Process In Lam Metastasismentioning
confidence: 99%
“…A previous study demonstrated that amiloride inhibited the uPA-uPAR pathway in a mouse lung tumor model [17]. Next, to determine whether the uPA-uPAR pathway contributes to the ability of SPD to promote skin wound healing, we intraperitoneally administered amiloride (10 mg/kg) daily.…”
Section: Upa-upar Signaling Regulates the Effect Of Spermidine On Skimentioning
confidence: 99%